Development of a HOTS-Based Ethnomathematics Module of the Sasambo Tribe on Spatial Geometry for Elementary School Students - Istiningsih, Siti; Dewi, Nurul Kemala; Erfan, Muhammad; Wulandari, Riska; Herlina (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop a valid and practical HOTS-based ethnomathematics module rooted in the cultural context of the Sasambo Tribe to enhance elementary school students' understanding of spatial geometry. The module demonstrates how cultural contexts can make abstract mathematical concepts more concrete and engaging, providing a model for integrating local wisdom into the national curriculum. The study employed a Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Quantitative data were analyzed using descriptive statistical techniques, with percentage scores calculated for each instrument. Qualitative data in the form of suggestions and comments from validators, students, and teachers were analyzed thematically to inform revisions at each stage. The validity test results indicated media validation at 92.4% and material validation at 94%, both categorized as highly valid. In the practicality test, the module achieved 92% in the small-group trial and 96.2% in the large-group trial based on student assessments, while teachers’ evaluations reached 100%, indicating a highly practical classification. The findings revealed that integrating Sasambo ethnomathematics with a HOTS approach increased student engagement in learning. The study concludes that the developed module meets the criteria of high validity and practicality and is suitable for use as an alternative teaching material in elementary mathematics instruction. Its structured design facilitates straightforward implementation by teachers, enhancing cultural relevance and fostering critical thinking skills in the classroom.